Antimicrobial resistance profiles of Staphylococcus aureus isolated from dogs and cats in veterinary clinics in Vinh Long Province, Vietnam - Truong Phuc Vinh; Nguyen Minh Tri; Phan Nhan (Jurnal Medik Veteriner, 2026)
Staphylococcus aureus is a common cause of dermatological, wound, and reproductive tract infections in companion animals, and its increasing antimicrobial resistance poses challenges for effective treatment. Data on resistance patterns in small animals in the Mekong Delta remain limited. This study aimed to determine the prevalence of S. aureus in clinical samples from dogs and cats and to characterize the antimicrobial susceptibility patterns of the isolates. Clinical samples were collected from dogs and cats showing signs of infection at veterinary clinics in Vinh Long Province, Vietnam. S. aureus was isolated using Mannitol Salt Agar and identified by standard biochemical tests. Antimicrobial susceptibility was determined using the Kirby–Bauer disk diffusion method according to CLSI guidelines. Of the 32 clinical specimens examined, 62.5% were positive for S. aureus. The prevalence was higher in dogs than in cats and higher in females than in males. Skin exudates accounted for the largest proportion of positive samples. Among the 60 isolates tested, resistance to ampicillin was highest at 90%. Increased resistance was also observed for erythromycin and trimethoprim–sulfamethoxazole. Susceptibility remained moderate to high for chloramphenicol, tetracycline, and levofloxacin. Multidrug resistance was common, with 22% of isolates resistant to ≥6 antibiotics. S. aureus is a frequent pathogen in small-animal clinical cases in Vinh Long Province and shows considerable resistance to commonly used antibiotics. The high rate of multidrug resistance highlights the need for routine culture and susceptibility testing and supports the implementation of antimicrobial stewardship in veterinary practice.